PS 17-64 ADDITIONAL FACTORS ASSOCIATED WITH DIASTOLIC FUNCTION IN PATIENTS WITH ARTERIAL HYPERTENSION. (September 2016) - Torbas, Olena; Sirenko, Yuriy; Radchenko, Ganna; Rekovets, Oksana; Kushnir, Svitlana
Abstract : Objective: For many years it was believed that left ventricle hypertrophy (LVH) is one of the leading factors of diastolic dysfunction formation in patients with arterial hypertension (AH). The aim of the study was to analize other factors associated with DD formation in patients with AH. Design and method: We included 154 patients with AH (SBP 151, 1 ± 2, 03; DBP 93, 12 ± 1, 87), 52, 5% women and 47, 5% men. We measured left (LAI) and right atrial (RAI) indexes, left ventricular myocardium mass index (LVMMI), mitral valve (MVG) and aortic valve (AVG) gradients, diastolic dysfunction with E/A and E/E', deceleration time (Dt), the amplitude of the septal part of mitral annulus motion (Sm). Also we measured office SBP, DBP, height, weight, BMI, body surface area. According to E/E' ratio patients were divided into groups - more than 10 (n = 79) and less than 10 (n = 75). Results: Groups did not differ significantly according to theirs height, BMI, body surface area and office SBP and DBP. In group of patients with E/E'>10 LAI and RAI were significantly higher (30, 2 ± 1, 4 vs 26, 4 ± 1, 2, p = 0, 042), LVMI in these patients was also significantly higher (111, 8 ± 4, 1 vs 97, 9 ± 3, 0; p = 0, 07). There was also significantly higher MVG (6, 7 ± 0, 4 vs 4, 7 ± 0, 2; p < 0, 001) and AVG (16, 2 ± 1, 9 vs 11, 5 ± 1, 2; p = 0, 03). The amplitude of mitral annulus motion in these patients was significantly lower (8, 9 ± 0, 3 vs 10, 7 ± 0, 4; p = 0, 001). Dt was significantly higher in E/E'>10 group (274, 3 ± 11, 2 vs 232, 2 ± 11, 5; p = 0, 011). No significant difference in E/A and EF was found. In the main group LAI and RAI correlated significantly with E/E' (r = 0, 24, p = 0, 009 and r = 0, 193, p = 0, 041), moreover, this correlation with LAI remained significant even after correction for LVMMI (β = 0, 2; p = 0, 036). E/E' correlated with MVG (r = 0, 38; p = 0, 001) and AVG (r = 0, 30; p < 0, 001), that was also significant after amendment for LAI and EF (β = 0, 35; p < 0, 001). Conclusions: Atrial remodeling, MVG and AVG has an independent effect on DD profile in patients with AH.